Assessment of Response to Neoadjuvant Therapy Using CT Texture Analysis in Patients With Resectable and Borderline Resectable Pancreatic Ductal Adenocarcinoma - Borhani, Amir A.; Dewan, Rohit; Furlan, Alessandro; Seiser, Natalie; Zureikat, Amer H.; Singhi, Aatur D.; Boone, Brian; Bahary, Nathan; Hogg, Melissa E.; Lotze, Michael; III, Herbert J. Zeh; Tublin, Mitchell E. (American journal of roentgenology (1976), 2020)
The goal of this study was to assess the correlation between CT-derived texture features of pancreatic ductal adenocarcinoma (PDAC) and histologic and biochemical markers of response to neoadjuvant treatment as well as disease-free survival in patients with potentially resectable PDAC. Thirty-nine patients completed this prospective study protocol between November 2013 and December 2016. All patients received neoadjuvant chemotherapy, underwent surgical resection, and had histologic grading of tumor response. Similar CT protocol was used for all patients. Pancreatic (late arterial) phase of pre- and posttreatment CT scans were evaluated. Histogram analysis and spatial-band-pass filtration were used to extract textural features. Correlation between textural parameters, histologic response, biochemical response, and genetic mutations was assessed using Mann-Whitney test, chi-square analysis, and multivariate logistic regression. Association with disease-free survival was assessed using Kaplan-Meier method and Cox model. Pretreatment mean positive pixel (MPP) at fine- and medium-level filtration, pretreatment kurtosis at medium-level filtration, changes in kurtosis, and pretreatment tumor SD were statistically different between patients with no or poor histologic response and favorable histologic response ( < 0.05). Changes in skewness and kurtosis at medium-level filtration significantly correlated with biochemical response ( < 0.01). On the basis of multivariate analysis, patients with higher MPP at pretreatment CT were more likely to have favorable histologic response (odds ratio, 1.06; 95% CI, 1.002-1.12). The Cox model for association between textural features and disease-free survival was statistically significant ( = 0.001). Textural features extracted from baseline pancreatic phase CT imaging of patients with potentially resectable PDAC and longitudinal changes in tumor heterogeneity can be used as biomarkers for predicting histologic response to neoadjuvant chemotherapy and disease-free survival.